2021
DOI: 10.1128/aem.02326-20
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Community Succession of theZostera marinaRhizobiome after Transplantation

Abstract: Seagrasses can form mutualisms with their microbiomes that facilitate the exchange of energy sources, nutrients, and hormones, and ultimately impact plant stress resistance. Little is known about community succession within the belowground seagrass microbiome after disturbance and its potential role in the plant’s recovery after transplantation. We transplanted Zostera marina shoots with and without an intact rhizosphere, and cultivated plants for four weeks while characterizing microbiome recovery and effects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 112 publications
0
17
0
Order By: Relevance
“…Methanol is potentially exuded by seagrass as a waste product of metabolism (Crump et al, 2018; Nemecek‐Marshall et al, 1995). Methylophilaceae and Methylophagaceae utilize methanol as a source of carbon and energy (Doronina et al, 2014) and can also be found on seagrass roots and rhizomes at lower abundances (Crump et al, 2018; Martin et al, 2020; Wang et al, 2020). Methylotrophs can produce plant growth promoting hormones and may contribute to stress tolerance in terrestrial plants (Kumar et al, 2019); they may play similar functional roles in seagrass and marine plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methanol is potentially exuded by seagrass as a waste product of metabolism (Crump et al, 2018; Nemecek‐Marshall et al, 1995). Methylophilaceae and Methylophagaceae utilize methanol as a source of carbon and energy (Doronina et al, 2014) and can also be found on seagrass roots and rhizomes at lower abundances (Crump et al, 2018; Martin et al, 2020; Wang et al, 2020). Methylotrophs can produce plant growth promoting hormones and may contribute to stress tolerance in terrestrial plants (Kumar et al, 2019); they may play similar functional roles in seagrass and marine plants.…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanisms for community stability are uncertain, some host species can maintain their original microbiota after transplanting, while other species exhibit microbiota turnover (Ziegler et al, 2019). Other seagrass transplant experiments investigating belowground microbiota found that seagrass transplanted without its original rhizome microbiota (rhizomes were rinsed with seawater prior to transplanting) can recover its original microbiota within 14 days (Wang et al, 2020), suggesting that host characteristics determine the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm dynamics may be a particularly important determinant of the timescale of turnover in host-associated microbial communities. Rapid microbiota turnover, on the order of hours to days, has been demonstrated for highly disturbed or previously uncolonized host surfaces and substrates in marine systems including corals (Ziegler et al, 2017(Ziegler et al, , 2019, macroalgae (Rao et al, 2006;Longford et al, 2019), seagrass (Wang et al, 2021), artificial macroalgal substrates (Lemay et al, 2020;Weigel and Pfister, 2020) and marine particles (Datta et al, 2016). Long-term observations of transplanted marine hosts with mature and unmanipulated biofilms see more gradual microbiota turnover, if any.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the microbial constituents in seagrass restoration is likely even more important when using transplants from other regions, or transplants grown in ex situ nurseries, especially, as we show that microbial communities can differ over comparatively small spatial scales (<10 km). If microbes are not considered it is possible that transplants could be maladapted to their new environments, or suffer from transplantation shock (Wang et al, 2021) which could be a contributing factors leading to restoration failure (Vogel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%